Regime-dependent sovereign risk pricing during the euro crisis - Anne-Laure Delatte; Julien Fouquau; Richard Portes (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
Previous work has documented a greater sensitivity of long-term government bond yields to fundamentals in Euro area stress countries during the euro crisis, but we know little about the driver(s) of regime-switches. Our estimates based on a panel smooth threshold regression model quantify and explain them: 1) investors have penalized a deterioration of fundamentals more strongly from 2010 to 2012; 2) a key indicator of regime switch is the premium of the financial credit default swap index: the higher the bank credit risk, the higher the extra premium on fundamentals; 3) after ECB President Draghi's speech in July 2012, it took one year to restore the non-crisis regime and suppress the extra premium.
Keywords: E44; F34; G12; H63; C23; 330; European sovereign crisis; Panel Smooth Threshold Regression Models; CDS indices